"I wouldn't have joined if it wasn't online": understanding older people's engagement with teleyoga classes for fall prevention - Abby Haynes; Heidi Gilchrist; Juliana S Oliveira; Catherine Sherrington; Anne Tiedemann (BMC, 2022)
Abstract Background Yoga-based exercise is a promising strategy for promoting healthy ageing, with the potential to reduce falls and increase physical, cognitive and psychological wellbeing. Teleyoga (real-time yoga provided via interactive videoconferencing) can deliver yoga programs at scale, potentially reducing costs, increasing convenience, and reaching people who cannot attend studio-based classes. But better understanding of how older people perceive and engage with teleyoga is needed to optimise its design, implementation and promotion. Methods This study built on a previous realist process evaluation of the SAGE yoga trial which is testing the effect of a yoga-based exercise program on falls among 700 community-dwelling people aged 60 + years. In this second phase of evaluation we conducted focus groups with participants who had completed the SAGE program online and with the yoga instructors who were delivering it. We also conducted interviews with participants who had withdrawn from the trial. Six program theories developed in the earlier evaluation provided a framework for data analysis, supplemented by inductive coding and an analytical workshop. Results Participants described physical and psychological benefits from the SAGE teleyoga program. While noting that teleyoga cannot facilitate hands-on correction or the same quality of observation or interaction as studio classes, participants were highly appreciative of their yoga instructors' strategies for optimising visibility, instruction, social connection and therapeutic alliance, and for adapting to constrained home environments. Some participants argued that teleyoga was superior to studio classes due to its accessibility and convenience, its lower exposure to potential embarrassment about physical appearance or capabilities, and a reduced sense of peer competition and distraction. Our program theories applied across studio and online modes of delivery. Conclusion Teleyoga increases accessibility for people in diverse locations and circumstances; it provides a psychologically safer space which combats self-consciousness and unwanted competitiveness; it may enhance embodiment and mindfulness for some; and it has the potential to be offered relatively cheaply at scale which could support free or reduced price classes for people on low incomes and pensions, thereby encouraging a wider population to engage in yoga for healthy ageing and fall prevention.